2021
DOI: 10.1039/d1nj02929k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of mesoporous Pt@SAPO-11 via in situ encapsulation for the decarboxylation of oleic acid to prepare C8–C17 alkanes

Abstract: A series of mesoporous Pt@SAPO−11 catalysts with different Pt loadings were prepared using an in situ encapsulation process. These materials exhibited good topological structures and high Brunauer−Emmett−Teller (BET) surface areas...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
1
5
1
Order By: Relevance
“…In the present study, the weak characteristic Pt peaks observed in the XRD patterns can also be partly ascribed to the low Pt concentrations in these materials. The wide-angle XRD patterns obtained from the Pt@KIT−6/SAPO−11 catalysts were like those generated by the Pt@SAPO−11 specimens prepared by Liu et al, 21 meaning that the characteristic peaks related to SAPO−11 and the AEL structure also appeared. In addition, the present patterns exhibit obvious characteristic Pt peaks.…”
Section: Catalytic Reactionssupporting
confidence: 58%
See 3 more Smart Citations
“…In the present study, the weak characteristic Pt peaks observed in the XRD patterns can also be partly ascribed to the low Pt concentrations in these materials. The wide-angle XRD patterns obtained from the Pt@KIT−6/SAPO−11 catalysts were like those generated by the Pt@SAPO−11 specimens prepared by Liu et al, 21 meaning that the characteristic peaks related to SAPO−11 and the AEL structure also appeared. In addition, the present patterns exhibit obvious characteristic Pt peaks.…”
Section: Catalytic Reactionssupporting
confidence: 58%
“…In the present work, the catalyst with a SiO 2 :Al 2 O 3 molar ratio of 0.4 and a Pt loading of 0.8 showed the best catalytic performance and produced a yield of C8-C17 alkanes as high as 85.1%. This value was superior to the yield of 80.8% obtained using Pt@SAPO−11 prepared via in situ encapsulation 21 under the optimal conditions. This behaviour was attributed to the suitable mesoporous structure of this material, as well as its physical and chemical properties.…”
Section: Decarboxylation Of Oleic Acidcontrasting
confidence: 55%
See 2 more Smart Citations
“…Actually, long-chain alkyl trimethyl ammonium bromides (C n H 2 n +1 (CH 3 ) 3 NBr) are often used as mesoporogens in the synthesis of hierarchical SAPO-11 molecular sieves. 5,13,25,27,38–40 Unfortunately, how the alkyl chain length of the mesoporogen affects the physicochemical properties and catalytic performance of hierarchical SAPO-11 molecular sieves has not been systematically investigated. In this study, hierarchical SAPO-11 molecular sieves will be synthesized by using n -alkyltrimethylammonium bromides with different alkyl chain lengths from C 8 to C 16 as mesoporogens and analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), N 2 adsorption–desorption, transmission electron microscopy (TEM), NH 3 temperature-programmed desorption (NH 3 -TPD) and pyridine adsorption Fourier-transform infrared (Py-IR).…”
Section: Introductionmentioning
confidence: 99%